Inferring phylogenetic patterns of land snails of the genus Albinaria on the island of Dia (Crete, Greece). Issue 5 (3rd September 2017) - Dimopoulou, Aggeliki; Antoniou, Aglaia; Mylonas, Moisis; Vardinoyiannis, Katerina; Poulakakis, Nikos
Abstract : Albinaria (Gastropoda, Clausiliidae) is a pulmonate genus distributed around the north-eastern coasts of the Mediterranean. It is the most 'speciose' genus within the family of Clausiliidae, exhibiting a high degree of morphological and genetic differentiation, and serving as a model for several ecological, systematics and evolutionary studies. Nevertheless, many aspects remain uncertain mainly due to the large number of taxa whose classification has not yet been evaluated with solid synapomorphic characters. Thirty-one morphological species are currently recognized on the island of Crete and its satellite islets. Four of them ( A. retusa, A. torticollis, A. jaeckeli, and A. teres ) are distributed on the island of Dia (north of Crete); the first three are island endemics. Here, we combined mitochondrial and nuclear DNA information and Bayesian and Maximum Likelihood approaches to evaluate the phylogenetic relationships, and assess the genetic distinctiveness and cohesiveness of all described species of Dia Island. The produced phylogeny was not congruent with the morphological species, demonstrating a more complex pattern of speciation and diversification. Although each island endemic constitutes a monophyletic lineage, the number of island endemic species could be greater than the three currently recognized species so far ( A. retusa, A. torticollis, and A. jaeckeli ), since a newly discovered lineage (north-western part of the island), that morphologically differs from the populations of A. torticollis in the eastern part, and genetically is more closely related to A. jaeckeli, could be elevated to the species level. Considering the fourth species found on the island of Dia, A. teres is genetically highly variable, showing low geographic structuring due to either long-distance gene flow or retained ancestral polymorphisms, or a combination of both. Further work (analysis of more specimens and DNA data) both from Dia and Crete is indispensable in order to shed light on aspects of the evolutionary history of the genus in Dia.